2017
DOI: 10.12953/2177-6830/rcm.v8n2p82-94
|View full text |Cite
|
Sign up to set email alerts
|

Influência de temperatura e taxas de aquecimento na resistência mecânica, densidade e rendimento do carvão da madeira de Eucalyptus cloeziana

Abstract: RESUMO O uso da pirólise como forma de aproveitamento energético da biomassa e resíduos orgânicos vem sendo avaliada como uma alternativa aos combustíveis fósseis. O carvão gerado neste processo é altamente recalcitrante, e sua incorporação ao solo pode contribuir para o sequestro de carbono, além de também melhorar a qualidade do solo de uso agrícola. Este trabalho avaliou o efeito de diferentes condições de pirólise sobre as características físicas, como resistência mecânica, densidade e rendimento gravimétr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…A redução no rendimento gravimétrico do carvão, observada a 600 ºC, ocorreu devido à maior perda de L. F. F. da Silva et al massa resultante da degradação térmica dos constituintes do lenho a partir do incremento da temperatura final de carbonização. Outros autores, como Vieira et al 2013e Siebeneichler et al (2017), ao estudarem carvão vegetal de Eucalyptus spp., espécies muito utilizadas como matéria-prima para carvão vegetal, verificaram diminuição do rendimento em carvão com o aumento de temperatura. Moulin et al (2017) carbonizaram resíduos de madeira de ipê, em temperaturas de 500 a 700 ºC.…”
Section: De Acordo Comunclassified
“…A redução no rendimento gravimétrico do carvão, observada a 600 ºC, ocorreu devido à maior perda de L. F. F. da Silva et al massa resultante da degradação térmica dos constituintes do lenho a partir do incremento da temperatura final de carbonização. Outros autores, como Vieira et al 2013e Siebeneichler et al (2017), ao estudarem carvão vegetal de Eucalyptus spp., espécies muito utilizadas como matéria-prima para carvão vegetal, verificaram diminuição do rendimento em carvão com o aumento de temperatura. Moulin et al (2017) carbonizaram resíduos de madeira de ipê, em temperaturas de 500 a 700 ºC.…”
Section: De Acordo Comunclassified
“…The complete characterization of the wood and charcoal properties of the pre-selected genetic materials for the production of charcoal is presented in Table 4. The presence of materials usually not used in the charcoal production, such as Eucalyptus maidenii hybrids is verified (Pereira et al, 2013a;Vital et al, 2013;Trugilho et al;2015;Pereira et al, 2016;Santos et al, 2016;Carneiro et al, 2017b;Rocha et al, 2017;Siebeneichler et al, 2017). In this way, the importance of the incorporation of genetic materials not usual for the charcoal production, in programs of improvement of these companies is evident.…”
Section: Pre-selection Of Genetic Materialsmentioning
confidence: 90%
“…The average wall fraction of the fibers of the genetic materials was 63.38% and coefficient of variation of 7.62% (Figure 1). The genetic material with values above 60% of wall fraction (Siebeneichler et al, 2017) are considered potential for charcoal production. Among the analyzed materials, 40% did not fit this recommendation.…”
Section: /9mentioning
confidence: 99%
“…In addition to handling, generation of charcoal fines in masonry furnaces is also affected by the carbonization temperature. Siebeneichler et al (2017) found that the increase in both temperature and heating rate increases the occurrence of ruptures in the charcoal structure, consequently reducing their physical resistance.…”
Section: Charcoal Qualitymentioning
confidence: 99%
“…According to Dias Júnior et al (2016) and Noumi et al (2016), this would be the expected result of higher carbonization temperature, as higher temperatures result in higher fixed carbon content of the produced charcoal, and fixed carbon contents above 80% are observed above 500 °C. Moreover, Siebeneichler et al (2017) stated that the increase in the temperature reduces the charcoal resistance.…”
Section: /8mentioning
confidence: 99%